Bacteria in Surgical Smoke: A Self-controlled Laboratory Study Using Porcine Spinal Tissues. Issue 23 (1st December 2021) - Zhu, Zhenqi; Liu, Ning; Xia, Weiwei; Liu, Haiying; Wood, Kirkham B.; Wang, Kaifeng
Abstract : The year 2020 has seen a surge in surgical smoke evacuation legislation across the United States. Little is known about the biohazard level of such plume. Using porcine spinal tissues, this self-controlled laboratory study found viable bacteria within the surgical smoke 95% of the time. Abstract : Study Design: A laboratory study performed in a self-controlled fashion. Objective: The aim of this study was to examine whether "surgical smoke" generated by using the electrocautery on porcine spinal tissues could contain viable bacteria. Summary of Background Data: The year 2020 has seen a surge in legislation regarding surgical smoke evacuation in the operating room across the United States. Surgical smoke contains numerous toxic and carcinogenic substances, which spine surgeons and operating room staff are regularly exposed to. Although the smoke's chemical toxicity has been extensively studied, little is known about its biohazard level. Methods: The electrocautery was used to "operate on" 20 segments of porcine spinal tissues on a clean bench. In each operation, the generated smoke was captured with a swab, which was positioned above the surgical site and within the smoke, to obtain bacteria cultures. Two other swabs—a tissue swab (swabbing the porcine tissue itself) and a blank swab (swabbing an empty sterile bowl)—were collected as controls. The culture results were compared among the three groups. An additional experiment was conducted to see whether using a mask can reduce the "infection rate" of the swab. Results: Although all blank swabs tested negative, 95% (19/20) of the smoke swabs tested positive, with a total of nine bacteria species identified. The most prevalent species observed in the smoke swabs included Serratia liquefaciens, Lactococcus garvieae, and Hafnia alvei, and so on. Among the positive smoke swabs, 84% (16/19) had one or more bacteria species that were consistent with the cultures of their corresponding tissue swabs. Using a surgical or N95 mask reduced the "infection rate" of the swab. Conclusion: "Surgical smoke" generated by electrocauterization of porcine spinal tissues contains viable bacteria. Further research in actual spine surgery is needed next. Level of Evidence: N/A